Multilocal Hyperstitions in the Urbatecture of the City of El Alto - Bolivia - Susana, Calle Quispe Vania (MAJ - Malaysia Architectural Journal, 2025)
One of the defining features of the city of El Alto, Bolivia (at 4,150 meters above sea level), is the self-organized relationship of its inhabitants regarding their multilocal displacement logics, between their residences in the city and their identity roots maintained with the rural area. Therefore, the production of urbatecture (architecture + urbanism) is generated from trivalent logics (this notion surpasses the binary logical system in its yes or no relationship), which constitute its diversity and heterogeneity with a strong interdependence between the biosymbolic and its sociospace. Thus, the purpose of this article is the study of hyperstitions through the architecture colloquially known as “cholet,” to materialize desires in architecture without losing the cultural ties that derive from tradition. This architecture adapts, modifies, and generates a logic of socioeconomic reproduction through itinerant ecosystems related to the construction field. These logics are inherent to the public space as a formal continuous space, which, understood from the Aymara logic, transforms into a community space, through practices rooted in superstitions, myths, symbols, and readings that come from ancestral memory. The research method is a qualitative socio-spatial analysis, based on interviews and data collection from primary and secondary sources. The main results will contribute to the construction of hyperstition in Andean Aymara urbatecture from multilocal construction logics.